2007
DOI: 10.1042/cs20060311
|View full text |Cite
|
Sign up to set email alerts
|

Graded occlusion of perfused rat muscle vasculature decreases insulin action

Abstract: Insulin increases capillary recruitment in vivo and impairment of this may contribute to muscle insulin resistance by limiting either insulin or glucose delivery. In the present study, the effect of progressively decreased rat muscle perfusion on insulin action using graded occlusion with MS (microspheres; 15 mum in diameter) was examined. EC (energy charge), PCr/Cr (phosphocreatine/creatine ratio), AMPK (AMP-activated protein kinase) phosphorylation on Thr(172) (P-AMPKalpha/total AMPK), oxygen uptake, nutriti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 37 publications
0
17
0
Order By: Relevance
“…In these previous studies, reduced glucose storage capacity was associated with a reduction in recruitable CBV, measured by capillary xanthine-oxidase activity or CEU, in obese and insulin-resistant animals and humans (4,5,32). Furthermore, the importance of capillary recruitment for both glucose uptake and insulin delivery is supported by the reduction in insulin-mediated glucose uptake and insulin receptor signaling after graded microsphere occlusion of skeletal muscle microcirculation without a change in basal glucose uptake and insulin receptor signaling (31). In aggregate, these studies together with our data suggest that microvascular dysfunction is not simply a downstream consequence of DM.…”
Section: Discussionmentioning
confidence: 89%
“…In these previous studies, reduced glucose storage capacity was associated with a reduction in recruitable CBV, measured by capillary xanthine-oxidase activity or CEU, in obese and insulin-resistant animals and humans (4,5,32). Furthermore, the importance of capillary recruitment for both glucose uptake and insulin delivery is supported by the reduction in insulin-mediated glucose uptake and insulin receptor signaling after graded microsphere occlusion of skeletal muscle microcirculation without a change in basal glucose uptake and insulin receptor signaling (31). In aggregate, these studies together with our data suggest that microvascular dysfunction is not simply a downstream consequence of DM.…”
Section: Discussionmentioning
confidence: 89%
“…11, 12, 13, 33, 34, 35 Likewise, rodent studies have demonstrated a direct effect of capillarization on insulin action in skeletal muscles. 14, 15, 16, 36, 37 A decrease in CD is associated with a longer diffusion distance between the nutritional blood vessels and the skeletal muscle cells. This change would impede the delivery of glucose to the muscle cells and thereby decrease IS.…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14][15] Results from experimental and human studies have suggested that insulin-mediated changes in muscle perfusion can modulate insulin-mediated glucose uptake. 11,35 The action of insulin, also seen in the skin, 36 can favor insulin itself and glucose availability to cells. MD seems to be inversely associated with insulin sensitivity in subjects with fasting hyperglycemia.…”
Section: Microvascular Dysfunction In Obesitymentioning
confidence: 99%
“…Experimentally, it has been shown that graded occlusion of perfused rat muscle vasculature markedly impaired insulin delivery, insulin-mediated Akt phosphorylation and glucose uptake, suggesting a pre-receptor defect in the insulin signaling pathway. 11 Although not yet fully established in a clinical setting, endothelial and MDs, characterized by decreased responses to endothelial-derived relaxing factors (essentially, but not only, nitric oxide) and alterations of hemodynamic parameters such as the number of perfused capillaries and baseline red blood cell velocity, respectively, have been hypothesized as primary causes of IR. [12][13][14][15] In type 2 diabetes mellitus, MD has been well characterized in the coronary bed 16 and the skin, 17 but in the young uncomplicated OW/obese persons, the extent of microvascular damage, tested by a non-invasive method, namely, the nailfold videocapillaroscopy, and its interrelationship with clinical-anthropometrical-laboratorial parameters remains to be determined.…”
Section: Introductionmentioning
confidence: 99%